El tema de la descentralización en la transición hacia la democracia - Palma, Eduardo (Revista EURE - Revista de Estudios Urbano Regionales, 1985)
Palma argues that descentralization is not a linear and accumulative process, but on the contrary, it needs a "disruption moment". The author maintains that centralization feeds from the failure of descentralization. Because of this Chile could see descentralization indefinitely postponed. Í 